EKSPLORASI PEMBELAJARAN BERBASIS INKUIRI DALAM MEMAHAMI PECAHAN DESIMAL DI SEKOLAH DASAR - ‘Amalya, Ghinayatul; Ismiyanti, Yulina; Sari, Yunita (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
Mathematics learning in elementary schools often faces challenges in improving students' understanding of the concept of decimal fractions. Conventional methods that focus more on procedural memorization tend to be less effective in helping students understand the relationship between ordinary fractions and decimal fractions. This study aims to explore the effectiveness of the application of the inquiry learning model with the help of student worksheets (LKPD) based on puzzles in improving the understanding of grade 4 students of SD Islam Sultan Agung 4 on decimal fractions. This study uses a qualitative approach with a case study design, the subjects of the study were grade IV students who had difficulty understanding decimal fractions. Data were collected through observation, anchorage, and documentation, then analyzed using Miles and Huberman data analysis techniques. The results showed that the application of the inquiry learning model with LKPD based on puzzles significantly improved students' understanding by identifying the form of ordinary fractions to decimal fractions showing the place value of decimal numbers, converting ordinary fractions to decimal fractions, and comparing fractions using a number line. In addition, 85% of students found it easier to understand the concept of decimal fractions, 78% were more confident in working on problems, and 90% stated that learning became more enjoyable. Thus, the inquiry learning model with puzzle-based LKPD can be an effective alternative in improving students' understanding of decimal fractions.